Informative real-time UiTM’s bus mobile application based on global positioning system (GPS) / Nur Khairunisa Zulaikha Mohamad Iskandar Shah - Mohamad Iskandar Shah, Nur Khairunisa Zulaikha (2019)
A research project on a mobile application that locate the location of UiTM's bus to help the students of UiTM as the main passenger of the transport by providing them the information that they needed. The common problem of using the public transport as such is that the timing seems to be usually are not scheduled and this could waste the passenger time. The objective of this project is to design a mobile application that provide the real-time information of the bus location through Global Positioning System (GPS), to develop a mobile application that increases the efficiency of the bus as the transportation through the knowledge of the information and lastly is to test the functionality of the application in terms of applying the Global Positioning System (GPS) navigation. The target user for this application is the passenger of UiTM bus and the UiTM's bus driver. So, basically the scope area includes all route that is use by the UiTM buses. Therefore, with this application it is in hope of helping the passenger better.